Relationship between Cognitive Learning Outcomes and Student Entrepreneurial Motivation in Biology Subjects - Anjani, Aprilia Ika Dewi; Jufri, A. Wahab; Artayasa, I Putu; Jamaluddin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The demand for high-quality human resources is increasingly needed because the industrial world requires the readiness of prospective workers and the creation of more jobs. More entrepreneurial power is needed to create new jobs and cultivate the entrepreneurial spirit early. This study analyzes the relationship between cognitive learning outcomes and student entrepreneurial motivation in biology subjects in class XI MA NW Narmada. The type of research used is quantitative descriptive research with correlational research methods. The population in this study was female students in grades XI, totaling 198. The sampling method used purposive sampling with a sample of XI MIPA Putri class students totaling 88. The data collection method is a survey research method using a questionnaire on entrepreneurial motivation and report card documents. The data analysis technique used in this study is the Pearson product-moment correlation test. The results showed a significant relationship between cognitive learning outcomes and student entrepreneurial motivation, with a significance value of 0.035 (p < 0.05) and a correlation coefficient of -0.225. The correlation index is in a low category so that the relationship between the two variables is negatively correlated and classified as low, which indicates that if the value of entrepreneurial motivation is high, the student's cognitive learning outcomes are low, and vice versa if the learning outcomes are high, the value of entrepreneurial motivation is low.